No escurinho do cinema, uma luz de moral cristã em Palmeira dos Índios-AL (1950-1970) - Silva, Maria Viviane de Melo (2018)
Cinema by its very nature abstracts people from reality. It provokes rush and nourishes tensions. In this sense, institutions organized around a faith, such as the Catholic Church, since the beginning of the twentieth century, saw in the cinemas their exhibited content and their social impacts as places that needed to undergo moral vigilance, under pain of their members become perverted by reason of contact with films that were not suited to their creed. Considering the presence of three cinematographic exhibition halls in Palmeira dos Índios-AL, during the 1950s and 1970s, we aimed to understand the Church's position in relation to them, analyzing the relationship between cinema and Christian morality, from a perspective of the history of the place and its transversality with cultural history. Based on the study of the reception of films linked to catholic interference, we tried to understand how the frequency with the cinemas influenced the daily life of the people and acted in the social formation of people of Palmeira dos Índios city. Based on the premises of Cultural History, we analyze the documentation that includes, mainly, the Catholic Newspaper O Semeador and the Juventude Palmeirense Journal, which contains articles criticizing the movies as well as periodicals, official documents, films exhibited at the time and other records. The results of the research point to the dissemination of the influence exerted by the Catholic Church in relation to the films and the public that attended the exhibition rooms in Palmeira dos Índios, Alagoas, evidencing its vigilant and moralizing attitude to society.